Global Wheat Production 2018
DOI: 10.5772/intechopen.75926
|View full text |Cite
|
Sign up to set email alerts
|

Role of Osmolytes and Antioxidant Enzymes for Drought Tolerance in Wheat

Abstract: Plants are vital to life as their presence maintains ecosystem on this living globe. Environ mental stresses trigger multiple responses initiated by plant cells to save plant life, from altered gene expression up to changes in cellular metabolism to regulate plant growth rates, which lead to better crop yield. The production of different osmoprotectants like proline, glycine-betaine (GB), trehalose, and antioxidant enzymes like superoxide dis mutase (SOD), catalase (CAT), and ascorbate peroxidase has shown a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…The mechanism by which the most tolerant genotypes seem to exhibit may be via (i) the mobilization of reserves of proteins during winter and beginning of spring periods, or (ii) the synthesis of amino acids, such as proline, as well as soluble proteins that can be involved in the protection against stress. For example in many studies, the synthesis of heat choc proteins, antioxidant enzymes, osmotically active metabolites, specific proteins and certain free radical enzymes were shown to control ion and water flux and support scavenging of oxygen radicals [21][22][23][24][25][26][27], thus allowing to confront and mend the disregulations at metabolism, molecular and cellular levels. Among other examples in literature, proline was shown to improve tolerance to stress including drought, salinity and heat [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which the most tolerant genotypes seem to exhibit may be via (i) the mobilization of reserves of proteins during winter and beginning of spring periods, or (ii) the synthesis of amino acids, such as proline, as well as soluble proteins that can be involved in the protection against stress. For example in many studies, the synthesis of heat choc proteins, antioxidant enzymes, osmotically active metabolites, specific proteins and certain free radical enzymes were shown to control ion and water flux and support scavenging of oxygen radicals [21][22][23][24][25][26][27], thus allowing to confront and mend the disregulations at metabolism, molecular and cellular levels. Among other examples in literature, proline was shown to improve tolerance to stress including drought, salinity and heat [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…For example in many studies, the synthesis of heat choc proteins, antioxidant enzymes, osmotically active metabolites, specific proteins and certain free radical enzymes were shown to control ion and water flux and support scavenging of oxygen radicals [21][22][23][24][25][26][27], thus allowing to confront and mend the disregulations at metabolism, molecular and cellular levels. Among other examples in literature, proline was shown to improve tolerance to stress including drought, salinity and heat [24][25][26][27]. It was also evidenced that proline synthesis was induced in stressed plants which in turn imparts stress tolerance by maintaining cell turgor or osmotic balance, [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported role of H 2 S in improving the antioxidative system to maintain ROS pool in the cells (Li et al , Kaya et al , Corpas et al ). During drought stress, it helps in the accumulation of osmolytes such as proline, betaine and trehalose in plants (Iqbal ).…”
Section: Introductionmentioning
confidence: 99%
“…Under drought tolerance, plants maintain turgor and persist metabolism in cells even at low water potential, mainly by synthesis of osmolytes or/and compatible solutes [3]. Production of different compatible osmolytes such as proline, glycine-betaine, trehalose, as well as antioxidant enzymes like superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) are proven to protect plant cells from immediate cellular damage by regulating gene expression level [4]. It is essential to analyze the function of drought stress-inducible genes enriched in drought related pathways, but there is also a need to understand the expression of genes that are related to drought stress avoidance.…”
Section: Introductionmentioning
confidence: 99%